2021
DOI: 10.3390/pr9081287
|View full text |Cite
|
Sign up to set email alerts
|

From Microbubbles to Nanobubbles: Effect on Flotation

Abstract: Attachment of particles and droplets to bubbles—the latter being of various fine sizes and created by different techniques (as described in detail)—forms the basis of flotation, a process which indeed was originated from mineral processing. Nevertheless, chemistry often plays a significant role in this area, in order for separation to be effective, as stressed. This (brief) review particularly discusses wastewater treatment applications and the effect of bubble size (from nano- to micro-) on the flotation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 72 publications
(84 reference statements)
1
13
0
Order By: Relevance
“…In addition, Calgaroto et al (2015) indicated that the most important mechanisms for NBs aiding the MBs flotation are the contact angle between contaminant particles and MBs was enhanced and the aggregation of particles was induced. It was reported that the combination of MBs and NBs has a high potential in removing pollutants from wastewater (Kyzas et al 2021).…”
Section: Rising Velocitymentioning
confidence: 99%
“…In addition, Calgaroto et al (2015) indicated that the most important mechanisms for NBs aiding the MBs flotation are the contact angle between contaminant particles and MBs was enhanced and the aggregation of particles was induced. It was reported that the combination of MBs and NBs has a high potential in removing pollutants from wastewater (Kyzas et al 2021).…”
Section: Rising Velocitymentioning
confidence: 99%
“…Heavy metal is one of the contaminants found in wastewater [4]. Anthropogenic sources such as electronics assembly and production, textiles, fertilizer and pesticide use, and mining operations all contribute to this wastewater with heavy metals [5] [6]. These heavy metals can be hazardous to species, including humans, even at low concentrations [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these approaches have drawbacks, such as metal removal that is insufficient [6]. It is critical that we find novel methods for the affordable, energy-efficient cleanup of trace pollutants from water in order to sustain environmental and human well-being [8] [9] .…”
Section: Introductionmentioning
confidence: 99%
“…The ore extracted from the mines of KGHM Polska Miedź S.A. contains, on average, about 1.52% of useful metal [3]. Valuable ore is subjected to processing, the main operation of which is enrichment by flotation [4][5][6][7]. As a result of this operation, a concentrate is obtained with a copper content enabling it to be metallurgically processed in the smelting process.…”
Section: Introductionmentioning
confidence: 99%
“…of which is enrichment by flotation [4][5][6][7]. As a result of this operation, a concentrate is obtained with a copper content enabling it to be metallurgically processed in the smelting process.…”
Section: Introductionmentioning
confidence: 99%